Development of Detailed Surface Reaction Mechanism of C2H4/C3H6 Oxidation on Pt/Al2O3 Monolith Catalyst Based on Gas Phase and Surface Species Analyses. Issue 7 (19th May 2022) - Naing, Set; Kristyawan, I Putu Angga; Murakami, Hiroshi; Hinokuma, Satoshi; Matsumoto, Yuhei; Omori, Tomohito; Wang, Yanlei; Yokohata, Hideaki; Kawano, Michiharu; Takebayashi, Hiroyuki; Miyoshi, Akira; Shimokuri, Daisuke
ABSTRACT: In this study, reaction characteristics of C2 H4 /O2 and C3 H6 /O2 on practical Pt/Al2 O3 monolith catalyst are investigated, and a simplified microkinetic surface reaction mechanism is proposed by taking the observed surface species and their occupied active surface sites into account. Importance of more than one active PGM surface site occupations at the adsorption step of C2 H4 or C3 H6 and multiple-sited stable intermediate CH x species are considered. Gas phase experimental results show that the light-off temperature as well as complete conversion temperature of both C2 H4 /O2 and C3 H6 /O2 mixture shift to lower side with the increase in oxygen concentration. The surface species analyses show the presence of stable intermediate CH x species and linearly adsorbed CO on the platinum surface. Numerically simulated light-off performance with the proposed reaction mechanism shows good agreement with the experimental results of C2 H4 /O2 and C3 H6 /O2 . Moreover, simulation results also agree well with the additional experimental results with multiple gas compositions and validate the proposed detailed reaction mechanism.